Evaluation of the optical switching characteristics of erbium-doped fibres for the development of a fibre Bragg grating sensor interrogator - Rigas, Evangelos; Correia, Ricardo N.; Stathopoulos, Nikolaos A.; Savaidis, S. P.; James, Stephen W.; Bhattacharyya, Debabrata; Kirby, Paul B.; Tatam, Ralph P. (SPIE - International Society for Optics and Photonics, 2014)
A polling topology that employs optical switching based on the properties of erbium-doped fibres (EDFs) is used to interrogate an array of FBGs. The properties of the EDF are investigated in its pumped and un-pumped states and the EDFs’ switching properties are evaluated by comparing them with a high performance electronically controlled MEM optical switch. Potential advantages of the proposed technique are discussed. © (2014) COPYRIGHT Society of Photo-Optical Instrumentation Engineers (SPIE). Downloading of the abstract is permitted for personal use only.
Keywords: FBG; Optical switching; Sensor interrogation; EDF; erbium-doped fibres